Faktor Perilaku dan Gaya Hidup yang Mempengaruhi Status Prediabetes Pasien Puskesmas Pati II - Ninik Trisnawati Sukenty; Zahroh Shaluhiyah; Antono Suryoputro (Master Program of Health Promotion Faculty of Public Health Diponegoro University, 2018)
Background: Prediabetes status describes as the condition of blood glucose level above normal but insufficient to be diagnosed as diabetes. The stage of prediabetes is a critical condition of blood glucose level, but could reverse to be normal again if healthy lifestyle is routinely performed. In USA one of three people diagnosed with prediabetes. But most people did not realize that they had prediabetes history. The increasing number of prediabetes occurs due to the absence of typical symptoms. If prediabetes detected earlier, the rate of diabetes mellitus could be prevented. This study aims to examine some behaviors that affect the prediabetes status of patients in Pati II health center. Method: This is an explanatory research with cross sectional approach. Samples were rucruited using inclusion criteria such as aged 40–59 years, not diagnosed as diabetes, abdominal circumference more than 90 for men and 80 for women. There were 117 respondents involved in this study. Results: This research showed that the number of respondents with prediabetes status was 39.3%. Respondents with blood glucose level ranged more than 200 mg/dl were 6%. The variables that influence the prediabetes status of the respondents were Body Mass Index with OR 3.591 (p value 0.011), diet pattern with OR 2.435 (p value 0.044), and smoking habit or passive smoking with OR 2.493 (p value 0.046). This study recommends to prevent the prediabetes to be diabetes, needed the socialization of healthy lifestyle to the community and early detection of prediabetes. Early prevention includes changes to people healthy lifestyles such as maintaining healthy body weight, doing physical activity routinely, healthy eating patterns, avoiding cigarette smoke and smoking habits.Keywords: prediabetes, BMI, diet, smoking